Improvement of the Logistics Flows in the Receiving Process of a Warehouse - Afonso Vaz de Oliveira; Carina M. Oliveira Pimentel; Radu Godina; João Carlos de Oliveira Matias; Susana M. Palavra Garrido (Logistics, 2022)
Background: The present work is related to a project developed in a company dealing with the security and communication systems, fire alarms, and electronic displays sector, located in the district of Aveiro. This work aims to improve the logistics flow of material reception in the warehouse of a company by using case study research methodology. Methods: Initially, there were too many queues at reception and high throughput times. The approach used to solve these problems was balancing the workstations, with the help of industrial simulation software (Arena®) and changing the existing layout, making the queues residual in order to reduce the throughput times. Results: Considerable savings were achieved with this approach in terms of operational costs. A reduction of the throughput time by 28% is reached and a reduced number of workstations is achieved, as well as a greater capacity to receive more material without the need for further investment. Conclusions: The changes in the layout allowed improvements at the ergonomic level and greater organization (5 S’s) at the workstations, thus having a positive impact on the employees’ working conditions.